A cross-national study : mergers and acquisitions practices in the banking industry in Japan and Germany. - Lim, Yvonne Zhiwen. (2011)
This paper compares the Mergers and Acquisitions (M&A) practices in the banking industry in Japan and Germany by means of two case studies from each country. We acknowledge the notion that Japan and Germany develop hybrid corporate governance systems and the extent to which they each adopt Anglo-American practices are different. However, we want to find out if the M&A practices are similar if they occur within the same industry in these two countries. Comparing the roles of the state (government and regulations), business (management) and labour (employees and union), we observe from our case illustrations that the processes and outcomes of the bank mergers in Japan and Germany are alike. We contend that the similarities can be attributed to the mergers occurring within the same industry. As such, we argue that M&A practices within the banking industry in Japan and Germany are similar. We explain how the abovementioned forces such as the state, business and labour have changed in the face of globalization, in terms of receptiveness towards M&A and increased understanding of the importance of M&A to stay globally competitive. We argue that the changes in the forces of state, business and labour will bring about similarities in banking M&A in Japan and Germany.